2021
DOI: 10.1108/yc-10-2020-1241
|View full text |Cite
|
Sign up to set email alerts
|

The effect of environmental concern on conscious green consumption of post-millennials: the moderating role of greenwashing perceptions

Abstract: Purpose This study aims to demonstrate how greenwashing perceptions shape the effect of environmental concern on post-millennials purchasing behavior. Design/methodology/approach Based on 174 responses gathered through a street survey method from 5 different universities in Turkey, data are analyzed using the statistical package for social sciences software (SPSS 16.0). Principal component analysis is performed to assess the differentiation in factors. Multiple regression analysis is used to examine the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 66 publications
(84 reference statements)
4
29
0
1
Order By: Relevance
“…This suggests that Greenwash has a detrimental impact on the environmental concerns of Indonesian Gen-Z customers. This is consistent with the findings of Bulut et al (2021), who discovered that the notion of greenwashing lowers the impact of environmental concern on green behavior. The H3 test results revealed that the findings were rejected.…”
Section: Structural Model and Hypothesis Testingsupporting
confidence: 92%
“…This suggests that Greenwash has a detrimental impact on the environmental concerns of Indonesian Gen-Z customers. This is consistent with the findings of Bulut et al (2021), who discovered that the notion of greenwashing lowers the impact of environmental concern on green behavior. The H3 test results revealed that the findings were rejected.…”
Section: Structural Model and Hypothesis Testingsupporting
confidence: 92%
“…This pro-environmental attitude is leaving a beneficial effect on environmental sustainability (Iqbal et al 2019 ) preservation, and production. According to research studies, altruism or altruistic motivation has a substantial positive impact on altering consumers’ motivation toward green consumptions, which has emerged among youth because of the use of social media (Mutum et al 2021 ; Bulut et al 2021 ; Gong et al 2021 ). According to Mainardes et al ( 2020 ), altruistic motivation can better create intrinsic motivation for caring and preserving the nature and environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They share information according to their likes and dislike on all possible forums to get all their friends, fellows, and family members on board. The forums can be physical discussions or gatherings, but the best forum can be social media including but not limited to Instagram, Facebook, and LinkedIn, where at the click of a button, you can pull information to a large audience (Moon et al 2018 ; Bulut et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The process of adopting renewable energy may be complex, necessitating the need to streamline the various processes to ensure the achievement of sustainability [20][21][22][23]. The consumer's willingness to adopt new renewable technologies depends on the complexities of using renewable energy.…”
Section: Ease Of Use (Eu)mentioning
confidence: 99%